Correlates of physical activity among people living with and without HIV in rural Uganda - Mabweazara, Smart Z.; Manne-Goehler, Jennifer; Bibangambah, Prossy; Kim, June-Ho; Ruth, Sentongo; Hemphill, Linda C.; Okello, Samson; Hamer, Mark; Siedner, Mark J. (Frontiers in Reproductive Health, 2023)
Background: Antiretroviral therapy (ART) has led to diminishing AIDS-related mortality but a concomitant increase in non-communicable diseases (NCDs) for people with HIV (PWH). Whereas physical activity (PA) has been shown to help prevent NCDs and NCD outcomes in other settings, there are few data on PA and its correlates among PWH in high-endemic settings. We aimed to compare PA by HIV serostatus in rural Uganda. Methods: We analysed data from the UGANDAC study, an observational cohort including PWH in ambulatory HIV care in Mbarara, Uganda, and age- and gender-matched people without HIV (PWOH). Our primary outcome of interest was PA, which we assessed using the International Physical Activity Questionnaire and considered as a continuous measure of metabolic equivalents in minutes/week (MET-min/week). Our primary exposure of interest was HIV serostatus. We fit univariable and multivariable linear regression models to estimate the relationship between HIV and PA levels, with and without addition of sociodemographic and clinical correlates of PA (MET-min/week). In secondary analyses, we explored relationships restricted to rural residents, and interactions between gender and serostatus. Results: We enrolled 309 participants, evenly divided by serostatus and gender. The mean age of PWH was 52 (standard deviation [SD] 7.2) and 52.6(SD 7.3) for PWOH. In general, participants engaged in high levels of PA regardless of serostatus, with 81.2% (251/309) meeting criteria for high PA. However, PWOH reported higher mean levels of PA met-minutes/week than PWH (9128 vs 7152, p=<0.001), and a greater proportion of PWOH (88.3%; 136/154) met the criteria for high PA compared to PWH (74.2%; 115/155). In adjusted models, lower levels of PA persisted among PWH (β = -1734, 95%CI -2645, -824, p = <0.001). Results were similar in a sensitivity analysis limited to people living in rural areas. Conclusion: In a rural Ugandan cohort, PWOH had higher levels of PA than PWH. Interventions that encourage PA among PWH may have a role in improving NCD risk profiles among PWH in the region.